RETRACTED: Innovative approaches to the feasibility study of options for calculation schemes of water supply - Khujaev Parviz; Bokiev Boki; Kholmurotov Turobqul; Murodov Parviz; Yakubov Alijon; Said Мajidzoda Tohir (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001